The influence of specific resistance training methodological prescription variables on strength development under hypoxic conditions: A systematic review and meta-analysis - Benavente, C.; Feriche, B. (Journal of Sports Sciences, 2025)
A systematic review and meta-analysis were conducted focused on the impact of specific methodological prescription variables in resistance training (RT) programming on muscle strength under hypoxic conditions. Searches of Pubmed-Medline, Web of Science, Sport Discuss and the Cochrane Library compared the effect of RT on strength development under hypoxic (RTH) vs. normoxic (RTN) conditions through the 1-repetition maximum (1RM) test. Apart from the overall meta-analysis, several RT methodological prescription variables available in the included studies (set end point, total weekly training volume, type of exercise, region of the body measured or type of routine) were analysed. Thirteen studies met the inclusion criteria. The overall analyses showed trivial differences in 1RM favouring RTH over RTN (SMD = 0.18 [CI: 0.04; 0.31]; p = 0.030). Sub-analyses revealed that a RT programme of a non-full-body routine, including 9 or more sets per exercise/week of multi-joint exercises performed to non-failure, favoured RTH for enhancing 1RM (p < 0.10). In conclusion, the evidence ratified a trivial benefit of RTH over RTN for muscle strength gains after a RT period. However, the handling of specific RT methodological prescription variables can slightly improve strength development outcomes in hypoxia.